Effects of Bambara groundnut and butternut blend on proximate, mineral, beta-carotene and folic acid contents of sorghum flour - Rosemary Kobue-Lekalake; Oduetse Daniel Gopadile; Gulelat Desse Haki; Eyassu Seifu; Moenyane Molapisi; Bonno Sekwati-Monang; John Gwamba; Kethabile Sonno; Boitumelo Mokobi; Geremew Bultosa (AIMS Agriculture and Food, 2022)
The refined sorghum flour (SF) used is limited in fiber and micronutrients because of bran removal during milling, and protein digestibility is poor due to kafrin crosslinking. In this research, the effects of Bambara groundnut (BG) (15%, 25%, 35%) and butternut (BU) powder (23%) blending on SF were investigated, using 100% SF as a control. The proximate, mineral, beta-carotene and folic acid compositions of the flour mix were determined. As the BG levels increased, the protein, fat, fiber, and ash contents increased significantly (p < 0.05), ranging between 8.62–14.19%, 2.36–3.38%, 1.37–3.04% and 0.87–2.19%, respectively. The iron, zinc, calcium and phosphorus contents in mg/100 g were 3.43–5.08, 2.96–3.74, 80.00–106.67 and 150.63–594.53, respectively. The beta-carotene (mg/100 g) and folic acid (μg/100 g) contents were < 0.01–0.63 and 0.75–1.42, respectively. The mineral, beta-carotene and folic acid contents of the flour mix varied significantly (p < 0.05) from the control. The pro-vitamin A beta-carotene content was improved in the blend flours with the addition of BU powder, whereas, in the control sample, it was not detected (<0.01 mg/100 g). With the 35% BG blend, increases of 37% protein, 45% crude fiber, 48% iron, 26% zinc, 133% calcium and 154% folic acid contents from the control were observed. The study showed food-to-food fortification of SF with BG flour and BU powder has the potential to combat malnutrition, and the public health challenges associated with deficiencies in bioactive fibers, proteins and micronutrients (pro-vitamin A carotenoids, folic acid and minerals).